Action research with parkrun UK volunteer organizers to develop inclusive strategies. (28th November 2019) - Fullagar, Simone; Petris, Sandra; Sargent, Julia; Allen, Stephanie; Akhtar, Muhsina; Ozakinci, Gozde
Abstract: This article addresses the challenge of promoting physical activity through a focus on equity and engaging physically inactive citizens through the development of inclusive strategies within parkrun UK—a free, volunteer-led, weekly mass community participation running event. We discuss how a UK-based action research design enabled collaboration with volunteer event organizers to understand participant experiences, constraints and develop localized inclusive practices. In contrast with 'expert'-driven health behaviour interventions, our research pursued a 'ground up' approach by asking what can be learnt from the successes and challenges of organizing community events, such as parkrun UK, to promote inclusion? A modified participatory action research approach was used with four parkrun sites across England, Scotland and Northern Ireland, that involved quantitative and qualitative analysis of survey data ( n = 655) that informed the process. Our analysis explored parkrunners' and volunteer organizers' perceptions relating to (i) the demographics of parkrun participation and (ii) actions for change in relation to the challenges of engaging marginalized groups (women, ethnic minorities, low income, older people, those with disabilities or illness). We discuss the challenges and opportunities for addressing (in)equity and inclusion through volunteer-based organizations and the implications for translating knowledge into organizational strategies.